Photovoltaic Properties of Bi2S3 and CdS Quantum Dot Sensitized TiO2 Solar Cells. (20th October 2015) - Esparza, Diego; Zarazúa, Isaac; López-Luke, Tzarara; Carriles, Ramón; Torres-Castro, Alejandro; Rosa, Elder De la
Abstract: Bismuth sulfide (Bi2 S3 ) is an attractive potential replacement for lead sulfide (PbS) due to its low toxicity and near infrared absorption spectrum. In this work, we report the photovoltaic characteristics of cadmium sulfide (CdS) and Bi2 S3 quantum dots (QDs) sensitized solar cells. The QDs were grown by the successive ionic layer adsorption and reaction (SILAR) method. The number of cycles was varied in order to optimize the photoconversion efficiency. Using a photovoltaic device with the structure TiO2 /CdS/ZnS as our reference, we obtained increments in the short circuit current (Jsc ) from 7.9 to 9.3 mA/cm 2, the fill factor (FF) from 41.9 to 53.7%, and the photoconversion efficiency (η) from 1.7% to 2.52% for the configuration TiO2 /CdS/Bi2 S3 /ZnS. This enhancement is explained by an augmented absorption spectral range and a favorable energy level diagram. Electrochemical impedance measurements were performed to better understand the carrier recombination and transport processes.